New heterobimetallic nickel(II) ferrocenyldithiophosphonato complexes: Syntheses, characterization, antiproliferative activity and X-ray, DFT, molecular docking studies on trans-bis-[O-3-methyl-1-butyl-(ferrocenyl) dithiophosphonato]nickel(II) - SAĞLAM, ERTUĞRUL GAZİ (ELSEVIER SCIENCE SA, 2021)
Ferrocenyldithiophosphonate type ligands in salt forms, ([NH4(FcLn)], FcLn = Fc(RO)P(S)S; n = 1, R = 3-phenyl-1-propyl-; n = 2, R = 1-phenyl-1-propyl-; n = 3, R = 3-methyl-1-butyl-; n = 4, R = 3-pentyl-) were prepared and reacting them with Ni(II) salts, complexes of the general formula [Ni(FcLn)(2)] were obtained. They were further treated with pyridine (Py) to yield [Ni(FcLn)(2)(Py)(2)]. X-ray structure of the complex, [Ni(FcL(3))(2)] was elucidated. The density functional (DFT) and docking calculations on the same compound were also performed by using X-ray data. Docking studies showed a notable van der Waals interaction between the complex [Ni(FcL(3))(2)] and human DNA. The cytotoxic activities of the compounds [Ni(FcLn)(2)] against three human cancer cell lines (HepG2, DLD-1, MDA-MB-231) were investigated for finding new drug candidates. The results indicate that [Ni(FcL1)(2)] and [Ni(FcL2)(2)] complexes have a mild degree of antiproliferative activity against liver, colon and breast cancerous cell lines. That the activity is mild indicate that the docking sites on DNA are not crucially active in malign reproduction.
Keywords: Ferrocenyl dithiophosphonato complexes; Cytotoxic activity; Anticancer; Molecular docking; X-ray; DFT; COORDINATION CHEMISTRY; CRYSTAL-STRUCTURE; STRUCTURAL-CHARACTERIZATION; CD(II) COMPLEXES; DITHIOPHOSPHONATE; LIGANDS; ZN(II); NI(II); FC